Mother-child communication during natural and artificial feeding in the aids age - Vasconcelos, Simone Gonçalves; Galvão, Marli Teresinha Gimeniz; Paiva, Simone de Sousa; Almeida, Paulo César de; Pagliuca, Lorita Marlena Freitag (Rev Rene, 2010)
When mothers with HIV breastfeed their children, this represents a risk factor to transmit the virus. Therefore, the exclusion of breastfeeding is recommended. Not breastfeeding can make communication between mother and child more difficult. A comparative study was carried out in the light of proxemic factors between mother and child during artificial feeding and breastfeeding among HIV-positive and negative women. At a rooming-in unit, 84 interactions between four mothers and their children were analyzed. Intimate distance prevails in 100% of the interactions, as well as the sitting posture. Babies of HIV-positive mothers remained active longer than vertically exposed babies. The quality of interactions over time and maternal responsiveness to the baby will probably determine repercussions of non-breastfeeding to the development of bonding between mother and child.